Thompson's Point, Charlotte, Vermont: A Platform for a folder of Nature Notes on a Website - Outwater, Anne H. (the Digital Archaeological Record)
Thompson’s Point on the Vermont side of Lake Champlain is an ecologically important peninsula about 1.5 miles long. Its dolomite cliffs support a rare upland natural community called Limestone Bluff Cedar-Pine Forest. Deep water, in combination with wide shallow bays surrounding the Point, make this one of Lake Champlain’s most important fishing grounds. Individuals at the Point have recently started a website: <www.thompsonspoint.org>. The website developers have agreed that a section of Ecological Notes would be useful. The purpose of this Capstone Project is to introduce the ecology of Thompson’s Point to owners and renters of camps on the Point, as well as provide a platform for future contributions about the natural features and phenomena of the peninsula. The area was traditionally inhabited by the Abenaki people and known as Kwezowahomak. More than 297 species specific Abenaki names are recorded for local flora and fauna; at least 67% of these species are known to occur on the Point. In the mid-1800s, European-Americans settled at the Point as a summer site for sport fishing and hunting. By 1900 most game birds, mammals, and fish were gone. The 230 acres of Thompson’s Point is now owned by the town of Charlotte and managed through land use regulations designed to preserve and protect the scenic beauty and the environmental quality of the land and lake. But in recent years, the site has been overrun by exotic invasive plants. Some camp owners have begun to remove the invasive plants and regeneration of native seedlings is occurring. Bird and mammal life is also regenerating. Technical assistance from the State of Vermont is available to guide restoration techniques and Abenaki species lists specific to the Point can guide camp owners to help return Thompson’s Point to its former glory.